(untitled) (Journal of Oriental Studies, 2017)
This article is about Massive Open Online Courses which is nowadays one of the new trends in higher education. Since South Korea is a leader in e-Learning development, the article emphasizes South Korean way of Open Education development. Authors describe the formation stages and further development of MOOC in South Korea. Also there was mentioned the development of Korean National K-MOOC platform which can be a good example and effective way for implementation of MOOC in Kazakhstan Higher Education System.